CD4/CD8 Ratio and the Risk of Kaposi Sarcoma or Non-Hodgkin Lymphoma in the Context of Efficiently Treated Human Immunodeficiency Virus (HIV) Infection: A Collaborative Analysis of 20 European Cohort Studies. (4th August 2020) - Caby, Fabienne; Guiguet, Marguerite; Weiss, Laurence; Winston, Alan; Miro, Jose M; Konopnicki, Deborah; Le Moing, Vincent; Bonnet, Fabrice; Reiss, Peter; Mussini, Cristina; Poizot-Martin, Isabelle; Taylor, Ninon; et al.
Abstract: Background: A persistently low CD4/CD8 ratio has been reported to inversely correlate with the risk of non-AIDS defining cancer in people living with human immunodeficiency virus (HIV; PLWH) efficiently treated by combination antiretroviral therapy (cART). We evaluated the impact of the CD4/CD8 ratio on the risk of Kaposi sarcoma (KS) or non-Hodgkin lymphoma (NHL), still among the most frequent cancers in treated PLWH. Methods: PLWH from the Collaboration of Observational HIV Epidemiological Research Europe (COHERE) were included if they achieved virological control (viral load ≤ 500 copies/mL) within 9 months following cART and without previous KS/LNH diagnosis. Cox models were used to identify factors associated with KS or NHL risk, in all participants and those with CD4 ≥ 500/mm 3 at virological control. We analyzed the CD4/CD8 ratio, CD4 count and CD8 count as time-dependent variables, using spline transformations. Results: We included 56 708 PLWH, enrolled between 2000 and 2014. At virological control, the median (interquartile range [IQR]) CD4 count, CD8 count, and CD4/CD8 ratio were 414 (296–552)/mm 3, 936 (670–1304)/mm 3, and 0.43 (0.28–0.65), respectively. Overall, 221 KS and 187 NHL were diagnosed 9 (2–37) and 18 (7–42) months after virological control. Low CD4/CD8 ratios were associated with KS risk (hazard ratio [HR] = 2.02 [95% confidence interval CI = 1.23–3.31]) when comparing CD4/CD8 = 0.3 to CD4/CD8 = 1) but not with NHL risk. High CD8 counts were associated with higher NHL risk (HR = 3.14 [95% CI = 1.58–6.22]) when comparing CD8 = 3000/mm 3 to CD8 = 1000/mm 3 ). Similar results with increased associations were found in PLWH with CD4 ≥ 500/mm 3 at virological control (HR = 3.27 [95% CI = 1.60–6.56] for KS; HR = 5.28 [95% CI = 2.17–12.83] for NHL). Conclusions: Low CD4/CD8 ratios and high CD8 counts despite effective cART were associated with increased KS/NHL risks respectively, especially when CD4 ≥ 500/mm 3 . Abstract : This study showed that CD4/CD8 ratio and CD8 count may help clinicians to identify treated People Living with HIV/AIDS with higher risk of developing Kaposi sarcoma and non-Hodgkin lymphoma, still among the most frequent cancers. These markers were particularly relevant when CD4 ≥500/mm 3 .